Analysis of Dietary Patterns and Food Security in Relation to Children's Nutritional Status in Central Sulawesi, 2021–2023 - Iskandar, Adi; Tanziha, Ikeu; Asri, Muthia Novita; Wulandari, Ashyfa Restu (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
A diverse and nutritious diet is essential to support good nutritional status. Nutritional issues such as stunting and wasting in Central Sulawesi are influenced by dietary patterns, food security, and vulnerability. The Food Consumption Pattern Score (Skor Pola Pangan Harapan or PPH) is used to evaluate the quality of dietary intake and its impact on nutritional status. This study aimed to analyze changes in PPH scores, food security and vulnerability indices, and their relationship with the nutritional status of children in Central Sulawesi from 2021 to 2023. This ecological study utilized secondary data from districts in Central Sulawesi, analyzed descriptively and through linear regression to assess variable relationships. The average PPH score remained stable, ranging from 77.2% to 80.6%. Both energy and protein adequacy levels improved in most areas, but wasting prevalence increased from 8.9% in 2021 to 13.0% in 2023. Regression analysis indicated that better dietary patterns and food utilization significantly reduced stunting (p < 0.05), while life expectancy had a significant effect in reducing wasting (p = 0.014). Research in Central Sulawesi (2021–2023) reveals a reduction in stunting from 28.9% to 27.0% but a rise in wasting from 8.9% to 13.0%. Key factors include access to clean water and effective food utilization, which lower stunting risk, while life expectancy reduces wasting. Stabilized Hope Food Pattern Scores (PPH) negatively correlate with stunting. Interventions should prioritize clean water access, food utilization, nutrition education, and public health programs to enhance life expectancy and reduce malnutrition.